Non-replicative Integral Membrane Proteins Encoded by Plant Alpha-Like Viruses: Emergence of Diverse Orphan ORFs and Movement Protein Genes - Solovyev, Andrey G.; Morozov, Sergey Y. (Frontiers in Plant Science, 2017)
Fast accumulation of sequencing data on plant virus genomes and plant transcriptomes demands periodic re-evaluation of current views on the genome evolution of viruses. Here, we substantiate and further detail our previously mostly speculative model on the origin and evolution of triple gene block (TGB) encoding plant virus movement proteins TGB1, TGB2, and TGB3. Recent experimental data on functional competence of transport gene modules consisting of two proteins related to TGB1 and TGB2, as well as sequence analysis data on similarity of TGB2 and TGB3 encoded by a viral genome and virus-like RNAs identified in a plant transcriptomes, suggest that TGB evolution involved events of gene duplication and gene transfer between viruses. In addition, our analysis identified that plant RNA-seq data assembled into RNA virus-like contigs encode a significant variety of hydrophobic proteins. Functions of these orphan proteins are still obscure; however some of them are obviously related to hydrophobic virion proteins of recently sequenced invertebrate (mostly insect) viruses, therefore supporting the current view on a common origin for many groups of plant and insect RNA-containing viruses. Moreover, these findings may suggest that the function of at least some orphan hydrophobic proteins is to provide plant viruses with the ability to infect insect hosts. In general, our observations emphasize that comparison of RNA virus sequences in a large variety of land plants and algae isolated geographically and ecologically may lead to experimental confirmation of previously purely speculative schemes of evolution of single genes, gene modules and whole genomes.